(untitled) - Duroselle, Jean Baptiste (New York and Evanston, 1968)
Contents: Part one The new diplomacy and its defeat 1913-1921, Part two The era of nationalism 1921-1933, Part three The roosevelt era 1933-1945
Keywords: Hoa Kỳ,United States; Quan hệ ngoại giao,Foreign relations; 1901-1953